The stress and workload of tour bus driver in Malaysia: striving for safer journeys / Joesri Mohamad Saber... [et al.] - Mohamad Saber, Joesri; Johari, Noorsa Riza; Ibrahim, Mohd Zoolfadli; Zulkifli, Nur Farahain (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Malaysia's thriving tourism industry relies on tour bus drivers to transport tourists to picturesque destinations and cultural hotspots across the country. While their occupation may appear glamorous, it is essential to secretly shed light on their daily obstacles. As the tour bus traverses Malaysia's diverse landscapes, transporting excited tourists to exotic locales and cultural treasures, the charismatic tour bus driver remains the unsung hero of the tourism industry. Behind the scenes lies a lesser-known reality: these devoted drivers face tremendous stress and workload. This article explores the stress and workload of tour bus drivers in Malaysia, highlighting the need for measures to ensure their health and, ultimately, passenger safety. According to Taklikar, (2016) and Chen & Hsu, (2020), tour bus driver stress and workload can be categorized into several factors: Demanding Work Hours: Tour bus drivers in Malaysia often endure long and irregular work hours, as tourist trips extend into evenings and weekends. They are tasked with handling both the transportation and guiding aspects of the journey, making their responsibilities multifaceted and exhausting. These extended work hours can lead to fatigue, affecting their alertness and responsiveness while on the road.